Preserving Bun Ya Ho Dance: A Bun Ya Ho Dance Procession Analysis in the Apitan Tradition in Kudus - Rafi Alfaris, Muh; Supriyanto, Agung (Jurnal Seni Tari, 2024)
Bun Ya Ho dance is a colossal dance brought by KH Abdul Jalil Tamyiz around the 1950s from Bumiayu, Brebes Regency. He responded to the condition of the Megawon community. At that time, many hobbies were contrary to religious law. The revitalization of Bun Ya Ho dance is based on the need for a typical Megawon art form to be performed on religious holidays, one of which is the Apitan tradition. The following note will explore more deeply the meaning and cultural values of the Bun Ya Ho dance procession in the Apitan (alms of earth) tradition in Megawon, Kudus Regency, the dynamics and challenges faced by dancers in the Bun Ya Ho dance procession, and the role of the younger generation of Megawon in preserving Bun Ya Ho dance. The research method carried out by researchers is literature. Results of this study explain that first, the meaning of Bun Ya Ho dance movements, namely: tayub (drunkenness) movement, war movement, and standing movement on a jug. Then, the cultural values in Bun Ya Ho dance are social value, aesthetic value, and educational value. Second, the dynamics of Bun Ya Ho dance, namely the dynamics of the Bun Ya Ho dance performers, the dynamics of the number of Bun Ya Ho dance personnel, and the dynamics of Bun Ya Ho Dance costumes. Third, the role of Megawon's young generation in preserving Bun Ya Ho Dance, namely paying attention and studying Bun Ya Ho dance, disseminating Bun Ya Ho dance information through social media, and participating in Apitan events actively.